The Effect of Population and Unemployment on Poverty and Economic Growth in South Sulawesi Province - Aulia Rahman B; Husnul Khatimah (Bulletin of Economic Studies (BEST), 2021)
Poverty and economic growth are important indicators to measure the achievement of regional development. To achieve inclusive development, each region will strive to optimize economic growth and reduce poverty. The purpose of this study is to analyze the effect of population and unemployment on economic growth poverty in South Sulawesi Province. This research is a type of quantitative research, using path analysis method. The results of the study found that the population has a direct and significant negative effect on poverty. Unemployment has a direct positive effect on poverty although it is not significant. Meanwhile, population and unemployment directly have a negative and significant effect on economic growth. Poverty directly has a negative but not significant effect on economic growth.  Finally, population and unemployment have a significant indirect effect on economic growth through poverty in South Sulawesi Province. The economic growth of South Sulawesi Province has not been inclusive in reducing the unemployment rate and alleviating poverty in this area.Keywords: Population, Unemployment, Poverty, Economic Growth.